Missing Piece Study protocol: prospective surveillance to determine the epidemiology of group A streptococcal pharyngitis and impetigo in remote Western Australia. Issue 4 (6th April 2022) - Barth, Dylan D; Mullane, Marianne J; Sampson, Claudia; Chou, Coco; Pickering, Janessa; Nicol, Mark P; Davies, Mark R; Carapetis, Jonathan; Bowen, Asha C
Abstract : Introduction: Group A β-haemolytic Streptococcus (GAS), a Gram-positive bacterium, causes skin, mucosal and systemic infections. Repeated GAS infections can lead to autoimmune diseases acute rheumatic fever (ARF) and rheumatic heart disease (RHD). Aboriginal and Torres Strait Islander peoples in Australia have the highest rates of ARF and RHD in the world. Despite this, the contemporaneous prevalence and incidence of GAS pharyngitis and impetigo in remote Australia remains unknown. To address this, we have designed a prospective surveillance study of GAS pharyngitis and impetigo to collect coincident contemporary evidence to inform and enhance primary prevention strategies for ARF. Methods and analysis: The Missing Piece Study aims to document the epidemiology of GAS pharyngitis and impetigo through collection of clinical, serological, microbiological and bacterial genomic data among remote-living Australian children. The study comprises two components: (1) screening of all children at school for GAS pharyngitis and impetigo up to three times a year and (2) weekly active surveillance visits to detect new cases of pharyngitis and impetigo. Environmental swabbing in remote schools will be included, to inform environmental health interventions. In addition, the application of new diagnostic technologies, microbiome analysis and bacterial genomic evaluations will enhance primary prevention strategies, having direct bearing on clinical care, vaccine development and surveillance for vaccine clinical trials. Ethics and dissemination: Ethical approval has been obtained from the Western Australian Aboriginal Health Ethics Committee (Ref: 892) and Human Research Ethics Committee of the University of Western Australia (Ref: RA/4/20/5101). Study findings will be shared with community members, teachers and children at participating schools, together with academic and medical services. Sharing findings in an appropriate manner is important and will be done in a suitable way which includes plain language summaries and presentations. Finally, findings and updates will also be disseminated to collaborators, researchers and health planners through peer-reviewed journal publications.